Effects of Injected Antibody against the Platelet Glycoprotein llb/llla Complex on Monkey Platelet Fibrinogen - Suzuki, Masahiko; Kawakatsu, Toshihiro; Nagata, Hirokazu; Hamamoto, Kenjiro; Iwata, Koji; Ohga, Shigetoshi; Nomura, Shosaku; Kokawa, Terutoshi; Yasunaga, Kojiro (Thrombosis and Haemostasis, 1992)
Four monkeys were injected for a 10-day period with the Fab fragment of a murine monoclonal antibody (NNKY 1-32) which inhibits the binding of fibrinogen to the platelet glycoprotein (GP) Ilb/IIIa complex. Platelet fibrinogen levels were assessed quantitatively by electroimmuno assay and qualitatively by immunoelectron microscopy.The platelet fibrinogen level fell to 9.0 ± 2.8% of the control level after antibody administration. Immunoelectron microscopy showed that the injected antibody was localized on the inner surface of the platelet a-granule membrane.Our findings suggest that the GP Ilb/IIIa complex can be internalized by a-granules and that it may mediate the endocytosis of plasma fibrinogen by platelets.